Efektivitas Penerapan Sistem Informasi dan Komputerisasi Haji Terpadu (SISKOHAT) dalam Penyelenggaraan Ibadah Haji - M Azlan; Nanda Miftahul Pariz (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
This research aims to analyze the effectiveness of implementing the Integrated Hajj Information and Computerization System (SISKOHAT) in organizing hajj pilgrimage at the Ministry of Religious Affairs Office of Dumai City. The research method used was field research with a qualitative descriptive approach through interview techniques and documentation with SISKOHAT operator staff. The research results show that the implementation of SISKOHAT has a significant positive impact in improving efficiency, accuracy, and transparency in hajj pilgrimage organization. This system successfully shortened registration and verification time, increased service capacity, and produced more accurate and updated pilgrim data. Information transparency also increased through integration with the Haji Pintar application that facilitates prospective pilgrims to monitor their registration status. However, the implementation of SISKOHAT still faces obstacles in the form of limited technological infrastructure and unstable internet networks, requiring improvements to optimize its use.